EFECTIVIDAD DE ESTRATEGIAS DIGITALES Y SU INCIDENCIA EN LA PROMOCIÓN DE EVENTOS CULTURALES EN LA CIUDAD DE BABAHOYO - CONTRERAS DIAZ, KATHERINE ANGELICA (2024)
Digital strategies have evolved over the years, this growth has been significant in various areas of society, because they are used to promote products, events or services. The purpose of this work is to analyze, evaluate and determine the effectiveness of digital strategies and their impact on promoting cultural events in the city of Babahoyo. Digital media are an important basis when disseminating cultural activities to guarantee community participation. Ecuador is a country distinguished by its diversity and has several cities recognized as cultural heritage. It is necessary to evaluate whether the strategies in Babahoyo are used appropriately. The methodology given is from a mixed and descriptive approach. It is essential to understand each type of research to apply appropriate strategies and obtain accurate and contextualized data on the phenomenon under study. The construction of this project is based on the bibliographic compilation of scientific articles and books from Google Scholar, focusing on the degree to which digital strategies have been received as an indispensable element to disseminate events. Surveys were also carried out among Babahoyense citizens, as well as an interview with the director of the House of Culture, Mr. Henry Layana Franco to learn his perspective on new technologies. This academic project is of utmost relevance to understand the tactics currently used in the city and propose new strategies to promote development, identity and local tourism. In addition, it will help organizers to find new ways to promote their events.